TESOL conference abstracts: discrepancies between potential writers‘ knowledge and actual composition - Nguyen Thi Thuy Loan; Li, Qian; Issra Pramoolsook; Nguyen Duy Linh (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
The ability to write a successful conference abstract seems to be one barrier preventing new researchers from disseminating their research work in their particular disciplinary community. However, very few studies on how conference abstracts are structured have been conducted in order to help such novice researchers. This study, thus, aims to examine the rhetorical structure of conference abstracts in two TESOL conferences in Asia with the purpose of informing a particular group of new researchers in Asian settings about the actual practice of writing this particular genre. The findings from the open-ended questions and the move analysis of 137 abstracts indicated that there was a mismatch between these potential conference abstract writers’ knowledge and the actual composition of these conference abstracts. Besides the rhetorical structures of conference abstracts, this paper also provided some pedagogical suggestions on dealing with this mismatch.